CULTURAL IDENTITY CHALLENGES IN THE ERA OF GLOBALIZATION - Olmasova Zahroxon Doniyorjon qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Globalization has become one of the most influential processes shaping contemporary societies. It affects economic development, political relations, and cultural interaction between nations. This article explores the impact of globalization on cultural identity and discusses the challenges of preserving language, traditions, and cultural heritage in the global era. The study also highlights the importance of education and cultural awareness in maintaining cultural diversity.